The shimmer [compact disc, unabridged] - Morrell, David. 1943- (Brilliance Audio, 2009)
When a high-speed chase goes terribly wrong, Santa Fe police officer Dan Page watches in horror as a car and gas tanker explode into flames. Torn with guilt that he may be responsible, Page returns home to discover that his wife, Tori, has disappeared. Frantic, Page follows her trail to Rostov, a remote town in Texas famous for a massive astronomical observatory, a long-abandoned military base, and unexplained nighttime phenomena that drew onlookers from every corner of the globe.